Performance Analysis f Regional Public Service Agency Abepura Regional Public Hospital Papua Province - Rumbiak, Darwin Kristian; Zainuri, Agus; Rantetoding, Septevanus; Tingginehe, Rosmin M. (Formosa Journal of Science and Technology, 2024)
The aim of the research is to analyze the performance of the Regional Public Service Agency, Abepura Regional General Hospital, Papua Province.This type of quantitative descriptive research with a sample size of 100 patients and 87 employees. Data was obtained using questionnaires and secondary data from the Abepura Regional General Hospital. The research results were obtainedperformance based on the patient's perspective regarding retention is considered good, but poor performance in patient acquisition results in a lack of patient satisfaction. Performance financial perspective revenue growthNPM (net profit) has increased well and there has been good efficiency and effectiveness after becoming a Regional Public Service Agency. The growth and learning perspective of employee retention and employee training is not good. Employee productivity is good with an increase in operating profit, but employee satisfaction is less satisfied.